Genetically engineered distal airway stem cell transplantation protects mice from pulmonary infection - Yue‐qing Zhou; Yun Shi; Ling Yang; Yu‐fen Sun; Yu‐fei Han; Zi‐xian Zhao; Yu‐jia Wang; Ying Liu; Yu Ma; Ting Zhang; Tao Ren; Tina P Dale; et al. (EMBO Molecular Medicine)
Abstract Severe pulmonary infection is a major threat to human health accompanied by substantial medical costs, prolonged inpatient requirements, and high mortality rates. New antimicrobial therapeutic strategies are urgently required to address the emergence of antibiotic resistance and persistent bacterial infections. In this study, we show that the constitutive expression of a native antimicrobial peptide LL‐37 in transgenic mice aids in clearing Pseudomonas aeruginosa (PAO1), a major pathogen of clinical pulmonary infection. Orthotopic transplantation of adult mouse distal airway stem cells (DASCs), genetically engineered to express LL‐37, into injured mouse lung foci enabled large‐scale incorporation of cells and long‐term release of the host defense peptide, protecting the mice from bacterial pneumonia and hypoxemia. Further, correlates of DASCs in adult humans were isolated, expanded, and genetically engineered to demonstrate successful construction of an anti‐infective artificial lung. Together, our stem cell‐based gene delivery therapeutic platform proposes a new strategy for addressing recurrent pulmonary infections with future translational opportunities.